Teaching and Learning English Using WhatsApp: (Narrative Inquiry of Senior High School Students in Mamasa West Sulawesi) - Chrismasari, Angeline; Kisman Salija; Sultan (International Journal of Business English and Communication, 2024)
This study in form of qualitative research by using narrative inquiry as a approach  in collecting data, that aim to find out (a) students’ perception  the way their teacher in teaching English using whatsapp, (b) students perception the learning English using whatsapp, (c) students challenges in learning English using whatsapp, and (d) students strategy to overcome their challenges in learning English using whatsapp. The participants of this research consisted of four students in the first grade of X MIA 2 in SMA N 1 Mamasa in 2020/2021 academic year. The instrument in collecting data was interview. The result of the interview analized by using three process, they are data reduction, data display and withdrawal/verification of conclusion. The results show that the students perception of the way their teacher in teaching English using whatsapp were making learning video, giving assignment, reviewing material, unsatisfying explanation, making q and a section, quite good explanation and initiative giving students time to ask. Students’ perception of learning English using whatsapp were Positive and negative perception. Students’s challenges in learning English using whatsapp were bad connection of network, must have internet quota, should have proper phone, not clearly understand, afraid to ask a question to teacher, inappropriate between material and  , phones’ storage is limited, and whatsapp is disorganized. Students’ strategy to overcome their challenges in learning English using whatsapp deleted unneeded files, giving star icon to files, arranging schedule, creating own whatsapp group, back up files, making and commitment for self. This study in form of qualitative research by using narrative inquiry as a approach  in collecting data, that aim to find out (a) students’ perception  the way their teacher in teaching English using whatsapp, (b) students perception the learning English using whatsapp, (c) students challenges in learning English using whatsapp, and (d) students strategy to overcome their challenges in learning English using whatsapp. The participants of this research consisted of four students in the first grade of X MIA 2 in SMA N 1 Mamasa in 2020/2021 academic year. The instrument in collecting data was interview. The result of the interview analized by using three process, they are data reduction, data display and withdrawal/verification of conclusion. The results show that the students perception of the way their teacher in teaching English using whatsapp were making learning video, giving assignment, reviewing material, unsatisfying explanation, making q and a section, quite good explanation and initiative giving students time to ask. Students’ perception of learning English using whatsapp were Positive and negative perception. Students’s challenges in learning English using whatsapp were bad connection of network, must have internet quota, should have proper phone, not clearly understand, afraid to ask a question to teacher, inappropriate between material and  , phones’ storage is limited, and whatsapp is disorganized. Students’ strategy to overcome their challenges in learning English using whatsapp deleted unneeded files, giving star icon to files, arranging schedule, creating own whatsapp group, back up files, making and commitment for self.